UV protection properties of workwear fabrics coated with TiO2 nanoparticles - Rabiei, Hadiseh; Farhang Dehghan, Somayeh; Montazer, Majid; Khaloo, Shokooh Sadat; Koozekonan, Aysa Ghasemi (Frontiers in Public Health, 2022)
The main purpose of this study was to evaluate the ultraviolet protective factor (UPF) of fabrics coated with TiO2 nanoparticles made using an in-situ synthesis method and more accurately assess the intrinsic properties of the textile. The cotton-polyester twill fabric (70–30%) (246.67 g/m2) was coated in-situ with TiO2 nanoparticles. In-situ coating is conducted in 4 steps; washing the fabrics, preparation of nanoparticles, injecting the nanoparticles into fabrics, and drying the fabric after coating. The scanning electron microscope (SEM) and X-ray diffraction (XRD), FTIR spectrometer, dynamic light scattering (DLS) and UV-Vis spectrophotometer were used to analyse the data of the coating and UPF results. Also, four standards such as ASTM D737, ISIRI 8332, ISIRI 4199, and ISIRI 567 were used for analyzing the intrinsic properties of a textile. The results of SEM, XRD and DLS altogether confirmed the in-situ formation of nanoparticles onto textile fibers. Moreover, the UPF value of the uncoated and coated fabrics was 3.67 and 55.82, respectively. It was shown that the in-situ deposition of TiO2 nanoparticles on fabric can provide adequate protection against UVR. Also, the results of analyzing the intrinsic properties of the textile showed that there were no significant differences in the intrinsic properties between the coated and uncoated fabrics. Based on the results, it can be concluded that the UV protective properties of workwear fabrics can be improved by coating TiO2 nanoparticles on them without any effect on the cooling effect of perspiration evaporation.